Transition metal coordination networks based on 1, 3-bis(1, 2, 4-triazol-1-yl)benzene and isophthalic acid: Luminescence and magnetic properties. (15th February 2018) - Shi, Xiu Juan; Chen, Peng Yun; Yin, Zhen Ming; Li, Tuo; Wu, Ming Ze; Tian, Li
Graphical abstract: Three new transition metal coordination polymers were obtained based on mixed multidentate ligands 1, 3-bis(1, 2, 4-triazol-1-yl)benzene (btb) and isophthalic acid (H2 ip).1 and2 show 2D networks with binuclear paddle-wheel structures.3 is confirmed as 1D double-chain ladder.1 and2 exhibit different magnetic behaviors.3 shows red-shifted luminescence spectra with obviously higher intensity. Abstract: Solvothermal reactions of 1, 3-bis(1, 2, 4-triazol-1-yl)benzene (btb), isophthalic acid (H2 ip) with M(NO3 )2 (M = Co 2+ (1 ), Cu 2+ (2 ), Cd 2+ (3 )) afforded three coordination polymers, [M(btb)(ip)] n (Co 2+ (1 ), Cu 2+ (2 )) and [Cd2 (btb)(ip)2 ·4H2 O] n ·4H2 O (3 ), respectively. Both compounds1 and2 show 2D networks with binuclear paddle-wheel structures, however3 is confirmed as 1D double-chain ladder. For complex1, weak ferromagnetic interactions are detected between Co II ions of Co2 unit without long-range magnetic ordering. Antiferromagnetic interactions are found between the Cu II centers in complex2 . In addition, complex3 shows red-shifted luminescence spectra with obviously higher intensity owning to the more rigid arrangement of the π systems.